Pilihan Habitat Kupu-kupu (Lepidoptera: Rhopalocera) di Sepanjang Sistem Agroforestri Taman Nasional Lore Lindu dan Kawasan Enklave, Sulawesi, Indonesia - Fitrallisan, Fitrallisan; R, Soleha; Yanti, Ria Rezki; Afrilianti, Cipta; Fitriana, Elif; Elijonnahdi, Elijonnahdi; Qodri, Agmal; Fahri, Fahri (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Butterflies are well-established bio-indicators for assessing biodiversity and monitoring ecosystem responses to environmental disturbances. Understanding their habitat preferences can help identify critical areas that require conservation to sustain their populations. This study aimed to determine butterfly habitat preferences across six land-use types in Lore Lindu National Park (natural forest habitats: primary forest, secondary forest, agroforestry, and river streams) and the Lindu and Besoa Enclave areas (anthropogenic systems: cocoa plantations and settlements). Butterflies were collected using insect nets with sweep netting techniques along transect lines in each habitat. Each habitat was divided into three 200-meter-long transects, sampled using purposive sampling. Butterfly habitat preferences in natural and anthropogenic habitats were evaluated by comparing the number of individuals and species, the percentage of families, and species composition across habitats. 1,786 individuals from 85 species across five butterfly families were recorded in Lore Lindu National Park and the surrounding enclave areas. The highest number of individuals and species was found in agroforestry habitats (527 individuals, 46 species). In contrast, primary forests had the lowest number of species (14 species), and river streams had the fewest individuals (76 individuals). The highest diversity index was found in agroforestry habitats (H' = 3.33, E = 0.75), while the lowest was in primary forests (H' = 2.27, E = 0.51). The Nymphalidae family had the highest percentage of species and individuals, distributed across all habitats. Species composition similarity among butterfly habitats grouped them into three categories: primary forest‒river stream, cocoa plantation‒settlement, and secondary forest‒agroforestry. Natural habitats (primary forests, secondary forests, agroforestry, and areas around river streams) supported a higher number of species compared to anthropogenic systems like cocoa plantations and settlements. Therefore, natural habitats are crucial for supporting butterfly populations in Lore Lindu National Park and its surrounding areas.